1990
DOI: 10.1093/protein/3.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Metallothioniens with interdomain hinges expanded by insertion mutagenesis

Abstract: Specific peptides of varying lengths were inserted between the two metal cluster domains of metallothionein (MT), which normally are spanned by only three amino acids, Lys-Lys-Ser. These interdomain expansions were made to test if such structural alterations would affect MT function. These constructs were engineered by inserting defined oligonucleotides of up to four tandem repeats of dodecanucleotides and hexanucleotides into an Alu-1 endonuclease cleavage site, which separates the two exonic regions of an MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Expression in yeast of mutant MTs possessing replacement of the interdomain lysine residues 30 and 31 with any combination of glutamine or glutamate residues (except Gln-Gln) resulted in wild-type copper and cadmium resistances (C. Cody and P.C.H., unpublished data). Similar results were obtained when up to four amino acids were inserted between the two MT domains (between Lys-31, and Ser-32) (34).…”
Section: Discussionsupporting
confidence: 79%
“…Expression in yeast of mutant MTs possessing replacement of the interdomain lysine residues 30 and 31 with any combination of glutamine or glutamate residues (except Gln-Gln) resulted in wild-type copper and cadmium resistances (C. Cody and P.C.H., unpublished data). Similar results were obtained when up to four amino acids were inserted between the two MT domains (between Lys-31, and Ser-32) (34).…”
Section: Discussionsupporting
confidence: 79%
“…This would result in a 6-and 4-amino acid putative link in wMT-1 and wMT-2, respectively. It has previously been shown that in vertebrates, an increase of the linker region reduces the overall stability of the MT molecule (25). Therefore, the observation that wMT-1 is less stable than wMT-2 would be consistent with a two-domain hypothesis in which the linker modulates the stability of the protein.…”
Section: Discussionsupporting
confidence: 67%
“…wMT-1 and wMT-2 (B) were purified by FPLC (C). The S tag-containing recombinant protein ran slightly slower than the native protein obtained previously (25).…”
Section: Resultsmentioning
confidence: 74%
“…As the linker is not involved in interdomain contacts it was suggested that it serves as a hinge region allowing a certain degree of domain movement [51]. The positive charge of the linker might also be required for charge neutralization as both domains bear a negative charge in their fully metalated form, i.e.…”
Section: Influence and Potential Role Of The Cys-devoid Linker Regionmentioning
confidence: 99%
“…2 for the -and 3 for the -domain when coordinated to four or three divalent metal ions, respectively. To study the effect of the length of the linker region, additional amino acid repeats consisting of Pro, Gly, and Asp residues were inserted C-terminal of the LysLysSer linker and metal tolerance assays performed in form of yeast complementation assays with accordingly transformed cell lines [51]. Insertion of up to 4 additional amino acids confers the same tolerance against up to 300 M Cd II ions as observed for the unmodified mammalian MT, constructs with longer inserts, i.e.…”
Section: Influence and Potential Role Of The Cys-devoid Linker Regionmentioning
confidence: 99%